PENDEKATAN DAKWAH DALAM MEMBINA PENGAMALAN AGAMA INA-INA: (Studi Kasus Ina-Ina Pedagang Kaki Lima Pasar Inpres Kota Palu) - Nur Wahidah Alimuddin (ISTIQRA, 2017)
Da'wah is meant to nurture Muslims especially those who have long embraced Islam but have not implemented the teachings of Islam in accordance with the provisions set by the Islamic religion. Thus, da'wah in particular is striving for messages of da'wah to mad, u and live in life, so that created the benefit of life not only in the world but more important in the afterlife. However, the reality of mad'u is shifting in value, so it is far from their own religion. Many people are crushed by the economic consequences of helplessness, so they spend their time just to seek a worldly life. Conditions like this that happens in some "ina-ina" street hawkers in the market Palu city inpres, so they drift with merchandise ranging from morning to evening without caring about the practice of religion that is believed. Based on the reality, the researcher will examine the practice of religious ina-ina street hawkers in the city market of Palu City and at the same time will examine the pattern of approach of da'wah appropriate for them so that they have comprehensive comprehension of religion and especially so that they can practice the teachings Islam in their daily lives, when and wherever they are